1995
DOI: 10.1007/bf01876091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting density of maize on the progress and spread of northern leaf blight fromExserohilum turcicum infested residue source

Abstract: Effect of plant density (37,037, 44,444 and 55,555 plants/ha) on the increase of northern leaf blight in time and space on two maize cultivars planted at spacings of 90, 75 and 60 between rows and 30 cm within rows was investigated. Exserohilum turcicum infested maize residue was used as an inoculum source. Maize density did not significantly affect the disease indices, but significantly influenced the grain yield of the two cultivars. In contrast, the two cuitivars differed significantly (P < 0.01) in diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The disease gradients varied significantly with year and location, being high in the second season and low in the first season of 2000 and second season of 1999, but were generally higher compared to those reported in other pathosystems (Lipps, 1988;Adipala et al, 1995) and on maize under temperate climatic conditions in Ohio, USA (de Nazareno et al, 1993b). According to Gregory (1968), secondary spread, background contamination or proximity to a large area of inoculum causes flattening of the primary gradient.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The disease gradients varied significantly with year and location, being high in the second season and low in the first season of 2000 and second season of 1999, but were generally higher compared to those reported in other pathosystems (Lipps, 1988;Adipala et al, 1995) and on maize under temperate climatic conditions in Ohio, USA (de Nazareno et al, 1993b). According to Gregory (1968), secondary spread, background contamination or proximity to a large area of inoculum causes flattening of the primary gradient.…”
Section: Discussionmentioning
confidence: 84%
“…The Gompertz model, ln(-ln(y)) = -ln(-lny) +rt (Berger, 1981), was also fitted to the pooled data from the four replicates. These models were selected because of their common usage and because most previous studies indicated their suitability (de Nazareno et al, 1993a,b;Takan et al, 1994;Adipala et al, 1995). Similarly, the exponential, y = a exp(-bx) (Kiyosawa & Shiyomi, 1972), and the power law model, y = ax b (Gregory, 1968), were fitted to the pooled data from the four replicates.…”
Section: Disease Progressmentioning
confidence: 99%
“…Northern leaf blight is a serious foliar disease of maize in the Northeastern United States, in sub-Saharan Africa, Latin America, China, and India (Adipala et al 1995;Dingerdissen et al 1996). A number of dominant or partially dominant major genes have been discovered conferring race-specific resistance to NLB, including Ht1 (Hooker et al 1963), Ht2 (Hooker 1977), Ht3 (Hooker 1981), Ht4 (Carson 1995), Htn1 (Gevers 1975), HtP (Ogliari et al 2005), and Bx (Couture et al 1971).…”
Section: Genes Conferring Resistance To Biotic Stresses In Maizementioning
confidence: 99%
“…NCLB is common in areas that have high humidity combined with moderate temperatures in the northeastern United States, in sub-Saharan Africa and in areas of China, Latin America, and India (Adipala et al, 1995 andDingerdissen et al, 1996). In India, the disease is prevalent in Karnataka, Andhra Pradesh, Tamil Nadu, Bihar, Himachal Pradesh, Maharashtra and other regions (Harlapur et al, 2000).…”
Section: Issn: 2319-7706 Volume 7 Number 06 (2018)mentioning
confidence: 99%